Tropical fruit by-products water extracts as sources of soluble fibres and phenolic compounds with potential antioxidant, anti-inflammatory, and functional properties. (January 2019) - Albuquerque, Marcela Albuquerque Cavalcanti de; Levit, Romina; Beres, Carolina; Bedani, Raquel; de Moreno de LeBlanc, Alejandra; Saad, Susana Marta Isay; LeBlanc, Jean Guy
Graphical abstract: Highlights: Mango water extract had the highest total phenolic content and antioxidant activity. Orange and mango water extracts decreased the highest levels of NO. Mango water extract stimulated the folate production by the co-culture TH-4 and LGG. All fruit by-product water extracts increased LGG adhesion to Caco-2 cells. Abstract: Fibre content, phenolic content, antioxidant and anti-inflammatory activities were evaluated for water extracts of fruit by-products (passion fruit, orange, acerola, and mango). The impact of these extracts on microbial growth, folate production, and adhesion ability of Streptococcus thermophilus TH-4 and Lactobacillus rhamnosus LGG was investigated. Mango water extract (MWE) presented the highest phenolic content and antioxidant activity. Orange water extract (OWE) and MWE showed the best anti-inflammatory potential by decreasing the highest nitric oxide levels. When TH-4 and LGG were grown together, folate production was only stimulated by MWE. Passion fruit water extract and OWE increased the TH-4 adhesion whereas acerola water extracts and MWE improved LGG adhesion when strains were used individually. These results showed that fruit by-product water extracts (FWE), especially from mango, presented potential beneficial biological and functional properties. These FWE could be used to develop new functional antioxidant foods and natural pharmaceutical ingredients.